POOR PARTICIPATION AND ALIENATED CITIZENRY: THE PROBLEM WITH DEVELOPMENT PROGRAMMES IN NIGERIA - Nwachukwun, Sunny; Tobechukwu, Nwachukwu Odunze; Nkem, Emenonye Henry (European Scientific Journal, ESJ, 2015)
Development is a programme, deliberate, concerted and sustained to free people from poverty, illiteracy, and disease and bring them into modern life. But citizen participation is a significant and necessary component of any attempt of improving the planning process of Development in Nigeria. This paper therefore investigates various approaches geared towards development and also their short comings. Among other causal factors; non participation of citizenry in developmental programme, planning, project choice is in a rarity hence a bane to development programme.